City History Study: Reconstruction of Sinabang City Infrastructure After the Tsunami, 2005-2009 - Raflis, Raflis (Riwayat: Educational Journal of History and Humanities, 2022)
This article knows the state of Sinabang City's infrastructure before the 2004 earthquake and tsunami disaster, and also gets a brief explanation of the impact of the 2004 Sinabang City earthquake and tsunami disaster, knowing the concept planned to reconstruct the infrastructure of Sinabang City after the 2005-2009 Tsunami. In this article, we use a qualitative type of approachin combination with historical methods. The technique data collection is carried out by means of documentation, literature studies and interviews. Analysis of the findings that Sinabang City before the 2004 tsunami was still under construction so that the infrastructure in Sinabang City was still simple and not yet comprehensive. Akibat disaster of the 2004 earthquake and Tsunami had an impact on the light damage to the existing infrastructure in Sinabang City, and there are 9 concepts that BRR plans to reconstruct the infrastructure of Sinabang City referring to the concept of a city spatial plan designed for Sinabang City.